Geographical variation of the chemical composition in essential oils extracted from Sardinian Salvia verbenaca. Issue 1 (22nd December 2021) - Mannu, Alberto; Melito, Sara; Petretto, Giacomo Luigi; Manconi, Paola; Pintore, Giorgio Mario; Chessa, Mario
Abstract: Salvia verbenaca is a perennial herbaceous plant well appreciated as medicinal herb which can be found in Mediterranean area, Europe, Africa and Asia. In this study, S. verbenaca flowers and leaves were collected in six different geographical areas of Sardinia (Italy). Information about the variation of the chemical composition of plants grown in different locations were obtained from gas chromatography analysis of the extracted essential oils. Gas chromatography analysis detected 33 compounds, which have been grouped in oxygenated monoterpenes, monoterpene hydrocarbons, sesquiterpenes and other compounds. The chemical composition of each group resulted significantly affected by sampling site in terms of geography and altitude. Concerning the geographical distribution of the detected chemicals, sesquiterpenes were found in considerable amount in three localities, monoterpenes hydrocarbons in two and other compounds were predominant only in one site. Regarding the altitude level, monoterpenes, sesquiterpenes and other compounds were predominant, respectively, at medium and medium-high altitude. Abstract : UF0001